Avaliação clínica de uma nova técnica cirúrgica para acesso e remoção de enxerto ósseo autógeno em bloco do mento mandibular - Pimentel Neto, Gonçalo Sobreira (2014)
The objective of this study is to present, through a prospective case series clinical research, a new surgical technique to access and remove block bone graft at the mandibular symphisis region, evaluating the morbidity for mental nerves. Forty patients requiring reconstruction of alveolar unit in the anterior maxilla were selected. A vertical incision was performed over the mandible bucal midline reaching the periosteum and a full thickness flap was raised with a tunneling technique. The bone block was removed with 8mm trephine drill positioned parallel to the mandible base and an angle of approximately 45 degrees with the external cortical bone, respecting anatomical limits. The donor site region was evaluated in a standardized clinical examination. Sensibility of the soft tissue innervated by mental nerves (ie, lower lip, infralabial area, and chin) was registered with esthesiometry (Semmes-Weinstein Monofilament Kit) in 15 Points measured before and after surgery (3, 7, 15 and 120 days). There were no reports of lower lip, infralabial area, or chin hypoesthesia. The midline vertical surgical access showed no mental nerve morbidity for this sample, and harvesting bone with trephine drill proved viable to single alveolar reconstruction